Neuromarketing Practices and Their Role in Raising the Efficiency of Marketing Performance - - Qutiba Amjad Abdul Ghafoor; Mohammed Edan Bani Al Khazraj (International Journal of Experiential Learning & Case Studies, 2024)
This research aims to diagnose the impact and contribution of Neuromarketing on the marketing performance of Sardar Automotive Trading Company and determine the nature of that relationship. To achieve this, the research seeks to understand the role played by Neuromarketing in enhancing overall marketing performance. Sardar Automotive Trading Company, a public company specializing in car and machinery trading, was chosen as the research site. A total of (58) questionnaires were analyzed, and distributed among a sample of marketing department managers and employees within the company, serving as the research sample. The data was analyzed using the statistical software SPSS, and a descriptive-analytical approach was adopted in conducting the research. The results indicated a significant relationship and correlation between neuromarketing and marketing performance. The research recommends that decision-makers within the company focus on marketing strategies based on the philosophy of Neuromarketing to influence customers, thereby achieving higher sales and greater profits, ultimately improving the entire marketing process